Un proyecto correccional femenino. Universo social y lógica institucional de la Cárcel del Buen Pastor, Córdoba 1892-1910 - Ornella Maritano; Melina Deangeli (Anuario de la Escuela de Historia Virtual, 2015)
The following paper deals with the phase of construction and implementation of the Female Correctional System in Córdoba (Argentina) through the case-study of the Female Prison and the House of the Buen Pastor between 1892-1910. This correctional project, which was administered by the Order of the Buen Pastor, stood aside from the punitive modernization. While it is possible to identify elements of reformist prison in the institution, we believe it presents, mostly, remnants of the administration of pre-modern way of punishment. In order to inquire into the features of this correctional project the research focused on the study of two main dimensions: the social universe and the institutional logic.